Pengaruh Influencer dan Kualitas Produk terhadap Keputusan Pembelian: Studi Kasus pada Bisnis Kuliner Repeat Hungry di Kota Bekasi (Jurnal Manajemen Kreatif dan Inovasi, 2026)
People's lifestyles utilizing social media have significantly enabled commercial brands to enhance promotion activities, often through the use of Influencers, which clearly present information regarding product quality and attract consumers to make purchasing decisions. This study aims to determine the extent of the influence of Influencers and product quality on purchasing decisions specifically at the Repeat Hungry culinary business in Bekasi. This research adopted a quantitative approach and was conducted at Comby Food Corner Repeat Hungry. Data was collected by distributing questionnaires to 100 Repeat Hungry customers using purposive sampling. The questionnaire results were measured using a Likert scale. Data analysis was performed using multiple linear regression with SPSS software. The findings of the Partial Test and Simultaneous Test indicate that both the Influencer variable and the product quality variable, either partially or simultaneously, possess a positive and significant effect on purchasing decisions. The research demonstrates that the positive influence of Influencers and high product quality, when executed concurrently and effectively, will lead to increased sales for the business. However, the study's scope was limited to promotion solely through the Instagram social media platform and involved samples only within the Bekasi area.